Firefighters' exposure biomonitoring: Impact of firefighting activities on levels of urinary monohydroxyl metabolites - Oliveira, Marta (2020)
The concentrations of six urinary monohydroxyl metabolites (OH-PAHs) of polycyclic aromatic hydrocarbons, namely 1-hydroxynaphthalene, 1-hydroxyacenaphthene, 2-hydroxyfluorene, 1-hydroxyphenanthrene, 1-hydroxypyrene (1OHPy), and 3-hydroxybenzo[a]pyrene, were assessed in the post-shift urine of wildland firefighters involved in fire combat activities at six Portuguese fire corporations, and compared with those of non-exposed subjects. Overall, median levels of urinary individual and total OH-PAHs (ΣOH-PAHs) suggest an increased exposure to polycyclic aromatic hydrocarbons during firefighting activities with ΣOH-PAH levels in exposed firefighters 1.7-35 times higher than in non-exposed ones. Urinary 1-hydroxynaphthalene and/or 1-hydroxyacenapthene were the predominant compounds, representing 63-98% of ΣOH-PAHs, followed by 2-hydroxyfluorene (1-17%), 1-hydroxyphenanthrene (1-13%), and 1OHPy (0.3-10%). A similar profile was observed when gender discrimination was considered. Participation in fire combat activities promoted an increase of the distribution percentage of 1-hydroxynaphthalene and 1-hydroxyacenaphthene, while contributions of 1-hydroxyphenanthrene and 1OHPy decreased. The detected urinary 1OHPy concentrations (1.73×10(-2) to 0.152μmol/mol creatinine in exposed subjects versus 1.21×10(-2) to 5.44×10(-2)μmol/mol creatinine in non-exposed individuals) were lower than the benchmark level (0.5μmol/mol creatinine) proposed by the American Conference of Governmental Industrial Hygienists. This compound, considered the biomarker of exposure to PAHs, was the less abundant one from the six analyzed biomarkers. Thus the inclusion of other metabolites, in addition to 1OHPy, in future studies is suggested to better estimate firefighters' occupational exposure to PAHs. Moreover, strong to moderate Spearman correlations were observed between individual compounds and ΣOH-PAHs corroborating the prevalence of an emission source.